Disparities in Rates of Fusions in Single-Level Lumbar Disc Pathologies. (1st September 2019) - Kim, Soobin; Ryoo, James S; Ostrov, Philip B; Reddy, Abhinav K; Mehta, Ankit Indravadan
Abstract: INTRODUCTION: Single-level lumbar disc pathologies are managed surgically through decompression (lumbar discectomy or laminectomy) and a potential fusion. However, there is a lack of evidence for or against fusion after decompression in specific patient populations. This study seeks to observe disparities in the rates of fusion after decompression. METHODS: Patients requiring surgical treatment for single-level disc herniation or degeneration were queried from the National Inpatient Sample datasets spanning 2012 to 2015. Multivariate logistic regression (with a Holm-Bonferroni correction) was performed to assess effects of patient demographics, temporality of admission, and hospital characteristics on rates of lumbar fusion while controlling for patient-level medical comorbidities. RESULTS: A total of 84 336 patients were included in the analysis of indicators for fusion after elective and nonelective surgical intervention for lumbar disc pathologies. Patients in private for-profit and not-for-profit hospitals were more likely to receive a fusion compared to those in public hospitals for elective cases (OR 1.20, P < .001; OR 1.21, P < .001, respectively). Nonelective patients in urban teaching and nonteaching hospitals were less likely to receive a fusion compared to those in rural hospitals (OR 0.49, P < .001; OR 0.54, P < .001, respectively). In both elective and nonelective cases, weekend admissions were less likely to receive fusions than weekday admissions (OR 0.35, P < .001; OR 0.46, P < .001, respectively). Compared to hospitals in New England, hospitals in East North Central, South Atlantic, and East South Central regions had higher rates of elective fusion (OR 1.29, 1.50, and 2.09, respectively; P < .001 for all), while hospitals in the Pacific and West South Central regions had lower rates of fusion (OR 0.56, P < .001; OR 0.50, P < .001, respectively). CONCLUSION: The results of this study illustrate disparities that exist in fusion after the surgical intervention of lumbar disc pathologies in terms of patient demographics and hospital characteristics.